A Diagnostic Nomogram for Predicting the Risk of Anastomotic Leakage in Elderly Patients With Rectal Cancer: A Single-center Retrospective Cohort Study. Issue 6 (21st December 2021) - Liu, Dongliang; Zhou, Hong; Liu, Liu; Zhu, Zhiqiang; Liu, Shaojun; Fang, Yu
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Laparoscopic resection for rectal cancer has been gaining popularity over the past 2 decades. Whether elderly patients had more benefits from laparoscopy-assisted anterior resection (LAR) need further investigation when comparing with open anterior resection (OAR). Objectives: This study aimed to evaluate the clinical outcomes and prognosis of LAR in elderly patients (65 y and above) with rectal cancer and investigate the factors associated with the anastomotic leakage (AL). Besides, the study sought to create a nomogram for precise prediction of AL after anterior resection for rectal cancer. Materials and Methods: A total of 343 rectal cancer patients over 65 years old who underwent LAR or OAR at a single center between January 2013 to January 2021 were retrospectively reviewed. Univariate analysis was conducted to explore potential risk factors for AL, and a nomogram for AL was created based on the multivariate logistic regression model. Results: A total of 343 patients were included in this study, 271 patients in LAR group and 72 patients in OAR group. Most of the variables were comparable between the 2 groups. The mean operative time was longer in the LAR group than that in the OAR group (191.66±58.33 vs. 156.85±53.88 min, P <0.0001). The LAR group exhibited a significantly lower intraoperative blood loss than the OAR group (85.17±50.03 vs. 131.67±79.10 mL; P <0.0001). Moreover, laparoscopic surgery resulted in shorter postoperative hospital stay, lower rates of diverting stoma and receiving sphincter sparing surgery in comparison with open surgery. The overall rates of complications were 25.1% and 40.3% in the LAR and OAR groups ( P =0.011), respectively. And the reoperation rates in the OAR group (0%) was lower than in the LAR group (1.5%), but the difference did not reach statistical significance ( P =0.300). Sex, location of tumor, diverting stoma and combined organ resection were identified as independent risk factors for AL based on multivariate analysis. Such factors were selected to develop a nomogram. After a median follow-up of 37.0 months, our study showed no significant difference in overall survival or disease free survival between the 2 groups for treatment of rectal cancer. Conclusions: This study suggests that LAR is an alternative minimally invasive surgical procedure in patients above 65 years with better short-term outcomes and acceptable long-term outcomes compared with OAR. In addition, our nomogram has satisfactory accuracy and clinical utility may benefit for clinical decision-making.